Synthesis Polyester Amide from Oleic Acid (Latakia University Journal -Basic Sciences Series, 2020)
In this article, a polyester amide was synthesized from oleic acid. This polymer is a biodegradable and thermoplastic polymer, with wide medical and biological applications due to its being compounds with a linear structure. The polymer structure has been confirmed. Output using spectroscopy methods known as 1H-NMR, and FT-IR spectroscopy. And we obtained this polymer with a good yield (78%).